Course info center (cic) / How Shih Wei - How, Shih Wei (2002)
Course Info Center ( CIC ) is a web-based system that bring out an easiest way for company's staff to find the information about the training courses search by their training's need. Chapter one of the report is showing out the introduction, objective, scope, and the reason why we build out the CIC system. The overview of the project in this chapter is considering the whole system's introduction. For the specific part, it can be found in Chapter Three and Chapter Four which are including the system analysis and system design. Before we make the decision to choose the development tools and determine the functional requirement, we have made a research by using different media and all the finding information can be found in Chapter two ---Literature Review. In this project, CIC system is constructed by a collection of independent but interacting subsystem --- the first part is considered about how a company sign in the system and how the system help the company's staff to search the training courses according to their training needs. In the another part, the part which is discussed in this report, is considered about how a training center sign in the system, how the system help the training center to provide the service of registering courses by company's staff, and what are the convenient that have been provided by the system to enhance the performance of the training center. The sub-topic in Chapter Three, Functional Requirement will discuss the functions that have been provided by the specific part of this system. The system not only provides the general functions like sign in and log in the system, keep the courses data in the database, and maintain the database, but it also including some functions for special requirements that can make the training center more easy to implement their task like provide online registration, calculate the payment and generate the invoice for the company, and analyze the most popular courses that have been registered by the company's staff. The precise of the system design about the architecture design, database design, process design, and interface design will describe in Chapter Four. CIC system is the combination of a company and training center. Through the system, the company's staff no need to waste their time in searching the training courses through the internet or another media by themselves. The training center will key in their information into the system and let the staff register courses directly. With the establishing of this system, training center just need to press a button to look through all the registration form from the company and process it. After that, the system will help them to calculate the payment that need to pay by the company after considering all the discount from the training center. These types of services automatically save a lot of time for the training center.